IDENTIFIKASI BAHAYA DAN PENGENDALIAN RISIKO KECELAKAAN KERJA DALAM PROSES DISTRIBUSI MINYAK MENTAH - MUHAMMAD RIZKI QUSYAHIRI; ATIDIRA DWI HANANI; SAMAT SAMAT (GANEC SWARA, 2024)
One type of work accident that often occurs is road transport accidents. The Ministry of Transportation shows a significant increase in the number of road transport accident victims from year to year. In 2022, the number of victims will reach 204,447 people, an increase of 33% compared to the previous year. During this period, 163,686 people recorded accident victims with minor injuries, 27,531 people died, and 12,230 people with serious injuries. This final assignment reviews identifying hazards and controlling the risk of work accidents in the crude oil distribution process at PT Sangkakala Niaga Energi in 2024. This research aims to identify potential hazards, analyze risk factors, and outline risk control measures. This type of research uses qualitative data research methods obtained from interviews, observations, and document analysis. From the results of the observation sheet, you can get an overview of the crude oil distribution process with 9 indicators and 73 statement items. The results of the observations identified 22 hazards and potential events in the crude oil distribution process. The Frequency Level (Possibility) and Severity Level (consequences) have various levels. There are 14 planned control actions that have been implemented, while there are 8 actions that do not include control actions. Researchers suggest that companies provide regular K3 training and disseminate knowledge about PPE in crude oil distribution work and provide sanctions for workers who violate company operational standards (SOP), can equip workers' facilities and provide action on hazards that have not received control measures so that safety programs and occupational health is going well